Ways to improve biocides for metalworking fluid - Di Martino, Patrick (AIMS Microbiol, 2021)
Metalworking fluids (MWF) are mainly emulsions of oil in water containing additives such as corrosion inhibitors, emulsifiers, defoamers, and biocides. Microbial contamination of MWF is almost systematic, and some of their constituents serve as nutrients for contaminating microorganisms. Biocides for MWF are protection products used to counter microbial contaminations and growth. Ideally, a biocide for MWF should have the following non-exhaustive criteria: have a broad-spectrum activity, be usable at low concentrations, be compatible with the formulation and the physical-chemical properties of MWF, be stable over time, retain its effectiveness in the presence of soiling, have no corrosive action on metals, present no danger to humans and the environment, be inexpensive. The future lies in the development of new molecules with biocidal activity corresponding to these ideal specifications, but in the meantime, it is possible to improve the performance of existing molecules currently on the market. Different strategies for potentiation of the activity of existing biocides are possible. The compatibility of the potentiation strategies with their use in metal working fluids is discussed.